Distinct influence of COX-1 and COX-2 on neuroinflammatory response and associated cognitive deficits during high altitude hypoxia. (1st March 2019) - Chauhan, Garima; Roy, Koustav; Kumar, Gaurav; Kumari, Punita; Alam, Shahnawaz; Kishore, Krishna; Panjwani, Usha; Ray, Koushik
Abstract: High-altitude hypoxia (HH) causes a spectrum of pathophysiological effects, including headaches, gliovascular dysfunction, and cognitive slowing. Previous studies have shown arachidonic acid (AA) metabolism due to cyclooxygenase (COX) activity before clinical manifestations in many diseases. AA metabolites, including COXs and prostaglandin E2 (PGE2), are well known immunomodulators. However, the relative contribution of COX-2 and COX-1 isoforms in the downstream proinflammatory responses and cognitive deficit in HH remains unknown. In the present study, AA metabolism via the COX pathway was investigated in Sprague Dawley rats after 0, 1, 3, and 7 days of HH exposure. Furthermore, we investigated the inflammatory response and cell-type-specific induction of both COXs. Our data revealed that AA metabolites peaked on day 3 of HH exposure. Interestingly, we observed endothelial and microglial activation on day 1, accompanied by an increase in the levels of proinflammatory cytokines, followed by astrocyte activation on day 3. We showed that the increase in COX activity during HH culminated in a significant increase in hippocampal inflammation, concomitant with spatial memory impairment and neuronal injury at day 7 of HH. We showed HH induced distinct COX-1 expression in endothelial and microglial cells, whereas it induced COX-2 expression predominantly in neurons, endothelial cells, and astrocytes. Notably, our data showed that the inhibition of COX-1 using valeryl salicylate had a prominent role in containing hippocampal inflammation by reducing microglial activation. COX-2 inhibition using celecoxib, along with COX-1 inhibition, ameliorated spatial memory impairment, astrocyte activation, and neurodegeneration after HH exposure. Graphical abstract: Image Highlights: COX pathway is augmented in a temporal manner during High altitude hypoxia (HH). Spatial memory deficits and neuroinflammation is evident after 7 days of HH. Cell-type-specific colocalization of COX-1 and COX-2 shows distinct role in HH. Both COX-1 and COX-2 inhibition ameliorated spatial memory deficits.